2011
DOI: 10.1152/jn.00895.2010
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity at rest: a multiscale hierarchical functional organization

Abstract: Spontaneous brain activity was mapped with functional MRI (fMRI) in a sample of 180 subjects while in a conscious resting-state condition. With the use of independent component analysis (ICA) of each individual fMRI signal and classification of the ICA-defined components across subjects, a set of 23 resting-state networks (RNs) was identified. Functional connectivity between each pair of RNs was assessed using temporal correlation analyses in the 0.01-to 0.1-Hz frequency band, and the corresponding set of corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
272
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 299 publications
(307 citation statements)
references
References 43 publications
30
272
3
2
Order By: Relevance
“…Specifically, we found that the functional network structure of individuals with higher levels of neuroticism is organized less optimally in terms of efficient information processing and consists of weaker functional connections. Furthermore, in high compared with low neurotic individuals, we showed that subnetworks related to emotion and salience processing have a more prominent role in the network organization, while subnetworks related to sensory(-motor) functions and cognitive control have a less prominent role (Doucet et al, 2011;Kinnison et al, 2012;Laird et al, 2011). This is in line with previous studies demonstrating that individuals with higher levels of neuroticism show more difficulties in adaptive emotion regulation (Suls and Martin, 2005;Watson and Hubbard, 1996;Yoon et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, we found that the functional network structure of individuals with higher levels of neuroticism is organized less optimally in terms of efficient information processing and consists of weaker functional connections. Furthermore, in high compared with low neurotic individuals, we showed that subnetworks related to emotion and salience processing have a more prominent role in the network organization, while subnetworks related to sensory(-motor) functions and cognitive control have a less prominent role (Doucet et al, 2011;Kinnison et al, 2012;Laird et al, 2011). This is in line with previous studies demonstrating that individuals with higher levels of neuroticism show more difficulties in adaptive emotion regulation (Suls and Martin, 2005;Watson and Hubbard, 1996;Yoon et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…for emotional instability: subnetworks related to emotion and salience processing have a more prominent role in the functional network organization of individuals scoring higher on neuroticism, while subnetworks that potentially control and regulate responses from these subnetworks have a less prominent role (Doucet et al, 2011;Kinnison et al, 2012;Laird et al, 2011). This is in line with evidence showing that high compared with low neurotic individuals experience more intense negative emotions, such as feelings of depression and anxiety, and demonstrate heighted emotional reactivity to negative events (Suls and Martin, 2005;Watson et al, 1994).…”
Section: Organization Of the Functional Subnetwork In Association Wisupporting
confidence: 74%
“…A novel method of functional network connectivity (FNC) analysis has previously been applied to resting‐state data [Allen et al, 2011; Doucet et al, 2011; Jafri et al, 2008]. Here, this FNC method was used in a task‐based study.…”
Section: Methodsmentioning
confidence: 99%
“…The time courses of remaining 53 components for each subject and condition, which were computed from the group ICA time courses by a PCA‐based back‐reconstruction method [Erhardt et al, 2011], were used for the following FNC analyses [Allen et al, 2011; Doucet et al, 2011; Jafri et al, 2008]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation